2019
DOI: 10.15644/asc53/3/8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Topographical Co-Cr-Mo Alloy Surface Changes After Various Finishing Treatments

Abstract: PurposeTo quantify the influence of three different finishing treatments on the cobalt-chromium-molybdenum (Co-Cr-Mo) alloy surface based on stereometric analysis parameters.Materials and methodsEighteen specimens were casted from an extra-hard alloy (Wironit®, BEGO, Bremen, Germany). The samples were distributed into three groups (n = 6 samples per group) dependent on different polishing techniques applied, as follows: A group, only electropolished (EP) samples; B group, after EP, an additional mechanical pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is because the metal helps withstand repeated chewing forces over time. To date, no studies have focused on process optimization of cobalt-based AM materials, specifically addressing the relationship between surface roughness and mechanical and frictional properties.. Further form of research related to this topic is found in the work of [33] research on surface finishing techniques by electromechanical polishing.…”
Section: Cobalt Chrome Alloysmentioning
confidence: 99%
“…This is because the metal helps withstand repeated chewing forces over time. To date, no studies have focused on process optimization of cobalt-based AM materials, specifically addressing the relationship between surface roughness and mechanical and frictional properties.. Further form of research related to this topic is found in the work of [33] research on surface finishing techniques by electromechanical polishing.…”
Section: Cobalt Chrome Alloysmentioning
confidence: 99%
“…As of now, there are no studies that focus on the processing optimization of AM cobaltbased materials with specific mention of surface roughness and its relation to tribological and mechanical-based properties. The closest form of research that touches on this topic can be found in a study by Ţălu et al, looking at post-surface-finishing techniques in the forms of electro-and mechanical-based polishing [126]. However, the aim of this study was only to focus on the final surface finish, rather than mechanical-or tribological-based performances.…”
Section: Cobalt Chrome Alloysmentioning
confidence: 99%
“…Due to their excellent mechanical properties with a combination of high wear, corrosion resistance, and biocompatibility, Co-Cr alloys are one of the standard materials in biomedical applications. In addition, Co-Cr alloys for dental appliances demonstrate optimal manufacturing, biomedical, and economic characteristics [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the SLM Co-Cr dental alloys, mechanical anisotropy was detected due to changes in the obtained microstructure [ 16 ]. The SLM-produced Co-Cr alloys met the properties according to the ISO 22674:2016 (type 5 criteria) such as UTS, yield strength, and elongation and were higher than manufactured by casting [ 1 , 2 , 3 , 27 , 28 , 29 , 30 , 31 ]. Therefore, optimizing the main SLM production parameters is essential for producing Co-Cr dental alloys with the necessary characteristics for dental appliances [ 3 , 26 ].…”
Section: Introductionmentioning
confidence: 99%